Seafloor magnetic lineation off the Otway/West Tasmania Basins:Ridge jumps and the subsidence history of the southeast Australiai margins - Veevers, J. J. (Australian Journal of Earth Sciences, 1988)
The seafloor off the Otway/West Tasmanian Basins has an east-west magnetic lineation attributable to seafloor spreading and notionally identified with the set of seafloor spreading anomalies A8-A20. Anomaly A20 (45 Ma) lies immediately south of a magnetic quiet zone that extends northward past the continent-ocean boundary (COB). The Southeast Indian Ocean has a constant angular width between the formerly conjugate margins of Australia and Antarctica, consistent with spreading that started along the entire margin about 96 Ma.The proximity of A20 to the Australian COB in some spreading ridge segments is therefore postulated as due to jumps of the spreading ridge to Australia with concomitant transfer of the older oceanic part of the Australian Plate to the Antarctic Plate. Accordingly, the age of the oldest seafloor at the COB in seven original ridge segments is estimated to step from about 96 to 82, 79, and 75 Ma. Break-up marks a change in the subsidence of the margin from rapid, during rifting by continental extension, to slow during thermal subsidence of the seafloor. Subsequent ridge jumps to the COB are expected to cause uplift or at least still-stand of the adjacent continental margin. The subsidence history of the Otway/West Tasmanian margin, as indicated by oil exploration wells, is sympathetic with the timing of the postulated ridge jumps in the adjacent seafloor, as is that of the Great Australian Bight Basin with adjacent seafloor to the west, and of the Bass and Gippsland Basins with the Tasman Sea adjacent to the east. The growth of structure at 80 Ma in the outer Gippsland Basin corresponds with a jump to Australia of the Tasman Sea ridge at 82 and 75 Ma, and at 65 Ma in the Great Australian Bight and Otway Basins to a ridge jump to Australia of the adjacent seafloor. The growth of structure at 60 Ma in the Bass Basin and at 55 Ma in the Gippsland Basin corresponds with the abandonment of the Tasman Sea ridge at A24 (55 Ma) during a re-organization of spreading in the southwest Pacific.